2019
DOI: 10.1111/jan.14149
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable patient‐related factors associated with pressure ulcers on the sacrum and heels: Secondary data analyses

Abstract: Aim To explore factors associated with the presence of category I–IV pressure ulcers on the sacrum and heels. Design Cross‐sectional, secondary data analysis using data collected from the Landelijke Prevalentiemeting Zorgproblemen (LPZ) project, a multicentre prevalence study including nursing home residents and community care clients (N = 4,842) in the Netherlands in 2017. Methods A single binary logistic regression model was designed to identify factors associated with the presence of pressure ulcers. Additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 50 publications
1
26
0
1
Order By: Relevance
“…The decrease in the number of PUs recorded may also be explained or influenced by the decrease in the mean age of the patients admitted to the study units during the pandemic, since age is considered to be a risk factor in developing PUs [ 21 ]. However, the number of PUs that occurred while in strict isolation in hospital is particularly worrying, since frequent patient repositioning and mobilisation avoid skin exposure to friction and are vital in PU prevention [ 24 ]. The study findings suggest that patient isolation may be associated with a decrease in the frequency of risk assessment and patient mobilisation, leading to decreased PU prevention.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in the number of PUs recorded may also be explained or influenced by the decrease in the mean age of the patients admitted to the study units during the pandemic, since age is considered to be a risk factor in developing PUs [ 21 ]. However, the number of PUs that occurred while in strict isolation in hospital is particularly worrying, since frequent patient repositioning and mobilisation avoid skin exposure to friction and are vital in PU prevention [ 24 ]. The study findings suggest that patient isolation may be associated with a decrease in the frequency of risk assessment and patient mobilisation, leading to decreased PU prevention.…”
Section: Discussionmentioning
confidence: 99%
“…For this review, they are reported as separate studies distinguished by the year of publication. Muntlin-Athlin et al (2016) (32) and Manderlier et al (2019) (33) were secondary analyses of HPU risk factors based on data collected from a randomised controlled trial (RCT) and a cross-sectional point-prevalence survey, retrospectively [33,34]. Table 1 provides further study characteristics of all eligible studies.…”
Section: General Study Characteristicsmentioning
confidence: 99%
“…Median HPU incidence rate was 17.4% (range: 2.9%-to 29.5%) based on the incidence rate from the four prospective and two retrospective cohort studies [29,32,[35][36][37][38]. Median prevalence was 11.7% (range: 1.5%-20.8%) based on the two cross-sectional studies and two retrospective case control cohort studies [30,31,31,33]. Across all studies, the participant population was diverse and included: patients from hospital wards with high HPU prevalence, a geriatric rehabilitation centre, major abdominal surgery, elective or trauma orthopaedic surgery, nursing homes and patients receiving community care.…”
Section: General Study Characteristicsmentioning
confidence: 99%
“…12 There is an international consensus on the consideration of PIs as an avoidable adverse event in healthcare (excluding the Kennedy terminal ulcers or other skin changes at life's end, that were considered as unavoidable injuries) 13 ; the National Quality Forum has included PIs in a list of reportable serious events categorised as an event that should never occur. 14 A number of factors have been associated with the development of PIs, some as aetiologic factors (friction, shear, pressure, moisture) 15 and others as risk factors (age, diabetes, malnutrition, poor circulation, blood disorders). 16 There are several models or frameworks that establish the relationships between these factors and their effect on the development of PIs.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%